A Porphyrinic Donor–Acceptor Conjugated Porous Polymer as Highly Efficient Photocatalyst for PET–RAFT Polymerization. Issue 18 (4th May 2022) - Zhao, Maoji; Zhu, Shuaishuai; Yang, Xue; Wang, Yong; Zhou, Xingping; Xie, Xiaolin
Abstract: Heterogeneous catalysts offer a highly desirable platform for exploring environmental‐benign transformation systems, yet, they typically suffer from significant loss of catalytic efficiency compared with their homogeneous counterparts. Here, the facile synthesis of a porphyrinic conjugated porous polymer incorporated with imidazolium bromide moieties by taking advantage of the Debus–Radziszewski reaction is reported. Owing to the unique donor–acceptor structure, this heterogeneous and metal‐free photocatalyst exhibits much improved catalytic activity compared with its small molecular analogs in photoinduced electron transfer reversible addition–fragmentation chain transfer (PET–RAFT) polymerization, producing polymers with narrow distribution ( Đ = 1.06–1.18) and high degree of chain‐end fidelity. Moreover, the heterogeneous catalyst can be easily separated at the end of polymerization by centrifugation and recycled for five independent PET–RAFT polymerizations without obvious decreases in catalytic efficiency. Abstract : A conjugated porous polymer with unique donor–acceptor structure is facilely synthesized in a one‐step procedure and exploited as a heterogenous and transition‐metal‐free photocatalyst for photoinduced electron transfer– reversible addition–fragmentation chain transfer polymerization. Notably, it exhibits much improved catalytic efficiency compared to its small molecular analogs and can be recyclable and reusable for 5 times without obvious loss of catalytic activity.